If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X + 33 = 4X + 31 Reorder the terms: 33 + 2X = 4X + 31 Reorder the terms: 33 + 2X = 31 + 4X Solving 33 + 2X = 31 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. 33 + 2X + -4X = 31 + 4X + -4X Combine like terms: 2X + -4X = -2X 33 + -2X = 31 + 4X + -4X Combine like terms: 4X + -4X = 0 33 + -2X = 31 + 0 33 + -2X = 31 Add '-33' to each side of the equation. 33 + -33 + -2X = 31 + -33 Combine like terms: 33 + -33 = 0 0 + -2X = 31 + -33 -2X = 31 + -33 Combine like terms: 31 + -33 = -2 -2X = -2 Divide each side by '-2'. X = 1 Simplifying X = 1
| 3x^2-2x-33=0 | | [x+3]=3 | | 16-9t^2=0 | | 3x-3=2x | | 6.4x-4.9x=-45 | | 5c^3=20c | | 9-5n+1=15 | | 4c+3-2c+7= | | 5x+6=4x+2 | | F=24l | | 4x+25=12x-55 | | (0)+3y=12 | | V^2+7v-18= | | 12x-29=7x+1 | | 8(3n+5)=-32 | | b+b+b+b= | | x+(x+1)+(x+2)=222 | | 3a+3b= | | 3b+3b= | | 9x-4y=-11 | | 3a+8a= | | 9n-28=53 | | -2(-5)(-10)= | | 2(x+5)=3(x-10) | | 22-5x=-28 | | 3x^2+2x-30=0 | | (-5)(10)= | | y+-4=-15 | | 3X^2+10X=-2 | | 9= | | 4a*9a= | | 96=2(6+2x)+2(x) |